Development and Validation of Online Nutrition Education Video EMPIRE (Emotion and Mind Power in Relationship with Eating) For Millennials with Overweight and Obesity - Khairizka Citra Palupi; Adela Eka Putri; Nadiyah; Laras Sitoayu (International Journal of Nursing and Health Services (IJNHS), 2021)
Overweight and obesity are still the biggest health problem in Indonesia, especially for the current millennial generation. The concept of mindfulness and mindful eating can be one of the intervention strategies to overcome overweight and obesity in this modern era. The study aimed to develop and validate the online nutrition education video EMPIE (Emotion and Mind Power in Relationship with Eating) for millennials with overweight and obesity. This study uses a 3-step method, namely, development (development of EMPIRE online nutrition education video materials), validation (validating content and constructs by 10 experts and 3 millennial respondents with overweight/obesity), evaluation (evaluation stage is not carried out by researchers due to time constraints). For construct validation using Pearson correlation and content validation using Content Validity Ratio (CVR) and Item-Level Content Validity Index (I-CVI) ?0,80. Validation consists of content, objective, relevant, motivational and construct components such as language and writing, illustrations, and quality. The content and construct validation of the EMPIRE nutrition education video (1,2,3,4,5) by experts and millennial respondents with overweight was declared valid with an overall average value of CVI ? 0.80. The content and construct components in the EMPIRE online nutrition education video are valid, so they are suitable to help overcome overweight and obesity among millennials